(3OQGSGJ eJbOeI aj GdeMGSHI GdVQjHjI (B:s (3MGdGJ hJWHjbGJ YedjI aj bjGS GdONd GdNGVY ddVQjHI (B/s - (3CHh MTjT, Ndjd YhGOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2004)
(3ebOeI aj JYQja GdVQjHI(B- (3GdNUGFU GdeejRI ddVQjHI Ydi GdONd aj GdCQOf(B- (3GdONd GdNGVY ddVQjHI(B- (3GdEYaGAGJ ef GdVQjHI(B- (3JMOjO GdQHM eMGSHjG hVQjHjG(B- (3JcGdja GdONd GdNGVY ddVQjHI(B- (3GdfabGJG ZjQ GdEfJGLjI(B- (3fabGJ GdONhd GdeYaGI hbhGYO QHWgG hJMUjdgG(B- (3VQjHI GdSMhHGJ(B- (3VQjHI GdaQhY(B- (3VQjHI YhGFO GdhOGFY(B- (3bjGS GdVQjHI GdeSJMbI Ydi eNJda Gdecdajf(B- (3GdWYf aj bQGQ JbOjQ VQjHI GdONd(B- (3GdJNdU ef GdVQjHI(B.s
(3GdeQGLY U(B. 563s
Keywords: (3GdVQGFH(B- (3GdeMGSHIs; (3VQGFH GdONd(B- (3GdeMGSHIs